Biochemical aspects of modified transdermal hormonal replacement therapy in the prophylaxis of atherosclerosis and vascular thrombosis in postmenopausal women - Stanosz, Małgorzata; Stanosz, Stanisław; Szczepiński, Jarosław Von Mach; Sieja, Krzysztof; Kościuszkiewicz, Jakub; Szczypiński, Dawid; Safranow, Krzysztof (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : The menopausal hormonal therapy (MHT) comprises hormonal replacement therapy (HRT) and hormonal supplement therapy (HST). In HRT, the structure of hormonal therapeutic agents is similar to natural hormones synthesized by ovaries. However, HST users are given hormones the structure and molecular weight of which are different from natural hormones. Objective : To evaluate the influence of modified hormonal transdermal replacement therapy (MHRT) and oral hormonal supplement therapy (HST) on the concentrations of estrogens, progesterone, prolactin, lipid fractions, lipoprotein (a), homocysteine, fibrinogen, C-reactive protein, C-protein, S-protein, antithrombin III in blood serum. The influence of this therapy on arterial blood pressure was also assessed. Material and methods : 70 healthy women aged 51-57 and divided into 2 groups [group I (n = 35) control received oral HST, and group II (n = 35)] were treated with modified transdermal hormonal replacement therapy (MHRT). The concentrations of sexual hormones were assessed by means of immunoenzymatic method, lipid fractions – the enzymatic method, and lipoprotein (a) – the immunoturbidimetric method, homocysteine concentration was assessed by the immunochemical method, antithrombin III – by the calorimetric method, fibrinogen and S protein were assessed by means of the clot method, and C-protein – by the kinetic method. Results : In users applying modified transdermal hormonal replacement therapy (MHRT), a significant decrease of concentrations of TC, LDL-C, lipoprotein (a), homocysteine, fibrinogen, C-reactive protein, and the increase of concentrations of HDL-C, PC-protein, PS-protein and antithrombin III in blood serum were found. This regimen did not increase arterial blood pressure. However, in users given oral hormonal supplement therapy (HST), an increase of concentrations of homocysteine, C-reactive protein, estrogens, prolactin and decrease of concentration of fibrinogen in blood serum were revealed. An increase of systolic blood pressure was observed. Conclusions : 1. In women receiving oral hormonal supplement therapy, a significantly high concentration of estrogens in blood serum compared to transdermal hormonal replacement therapy can be caused by their different distribution and metabolic disturbances. 2. The lack of changes in concentrations of some lipid and non-lipid parameters compared to the initial values in women receiving cyclic oral hormonal supplement therapy suggests the impaired liver function caused by the effect of “first passage” estrogens in the portal system.